2022
DOI: 10.1155/2022/9376885
|View full text |Cite
|
Sign up to set email alerts
|

A Method Applied in Anomaly Detection of Impurities Adhering to Pipes of Coriolis Mass Flowmeter

Abstract: The Coriolis mass flowmeter (CMF) is widely used to measure mass flow, mainly in petrochemical, medical, pharmaceutical, food manufacturing, and other industries. The measuring tube is the crucial component of CMF, which affects the measurement accuracy and causes losses to the production of enterprises. Wall-mounted failure of the measuring tube affects measurement accuracy. A real-time detection method based on acceleration sensor array signal processing and pattern recognition are proposed to detect such fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The CFM accuracy is supposedly aimed at being higher than 99.9% for multiphase fluids, including viscous fluids, emulsions, gases and bubbly flows [ 11 ]. However, several studies have shown that the gas in the flow may cause a drop in the CFM accuracy [ 7 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The CFM error at multiphase metering is assumed to be primarily caused by the decoupling effect according to several studies [ 16 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CFM accuracy is supposedly aimed at being higher than 99.9% for multiphase fluids, including viscous fluids, emulsions, gases and bubbly flows [ 11 ]. However, several studies have shown that the gas in the flow may cause a drop in the CFM accuracy [ 7 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The CFM error at multiphase metering is assumed to be primarily caused by the decoupling effect according to several studies [ 16 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%